Ileal and caecal microbial populations in broilers given specific essential oil blends and probiotics in two consecutive grow-outs - Oviedo-Rondon, Edgar O.; Hume, Michael E.; Barbosa, Nei A. [UNESP]; Sakomura, Nilva K. [UNESP]; Weber, Gilbert; Wilson, Johnathan W. (Science Reviews 2000 Ltd, 2010)
Specific essential oil (EO) blends and probiotics used as feed additives have been shown to promote healthy digestive microbials resulting in improved poultry production. Two consecutive experiments were conducted with broilers fed corn-soybean meal diets to determine comparative effects of feed additives on ileal and caecal microbial populations (MP). Ross 708 broilers were placed in 84 pens with previously used litter and treatments maintained in the same pens for both experiments. Eight treatment groups were fed diets containing: Bacitracin methylene disalicylate (BMD) as positive control (PC); no additives as negative control (NC); three probiotics: BC-30; BioPlus 2B (B2B); and Calsporin; and the essential oil blends Crina Poultry Plus (CPP) at 300 or 150 ppm in the first experiment; and CPP at 300 ppm and Crina Poultry AF at 100 ppm in experiment 2. Starter and grower diets contained the ionophore (Coban). Ileal and caecal samples were collected at 43 days of age from male broilers. The DNA of microbial populations was isolated from digesta samples and analysed by denaturing gradient gel electrophoresis to generate percentage similarity coefficients (%SC) from band pattern dendrograms. Differences were observed in ileal and caecal populations depending on treatment, respectively, and especially between experiments. Broilers fed diets with probiotics had very similar MP. The EO CPP at 300 ppm resulted in ilea! MP similar to those observed in chickens fed probiotics. We concluded that antibiotic treatment affected ileal, but no caecal MP. More pronounced changes in ileal and caecal MP were seen in broilers at 43 days of age following probiotic and essential oil treatments.
Keywords: essential oils; probiotics; microbial ecology; built-up litter; denaturing gradient gel electrophoresis